2012
DOI: 10.1590/s1415-47572012005000001
|View full text |Cite
|
Sign up to set email alerts
|

Medium-sized deletion in the BRCA1 gene: limitations of Sanger sequencing and MLPA analyses

Abstract: We describe a family with a history of breast and ovarian cancer in which MLPA analysis of the BRCA1 gene pointed to a deletion including a part of exon 11. Further characterization confirmed a loss of 374 bp in a region completely covered by conventional sequencing which had not revealed the deletion. Because this alteration was only detected serendipitously with an MLPA probe, we calculated the probabilities of detecting medium-sized deletions in large exons by methods including initial PCR amplification. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…While Sanger sequencing is reliable to detect single point mutations, which are various and frequent in MM and other cancer types 5, 8, 21, 26, 30, 31 , the MLPA assay is much more reliable to detect large deletions 32 . We found that Sanger sequencing was very reliable and reproducible in detecting BAP1 point mutations and small deletions in preparations of DNA from laser dissected MM biopsies containing over 80% purity of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…While Sanger sequencing is reliable to detect single point mutations, which are various and frequent in MM and other cancer types 5, 8, 21, 26, 30, 31 , the MLPA assay is much more reliable to detect large deletions 32 . We found that Sanger sequencing was very reliable and reproducible in detecting BAP1 point mutations and small deletions in preparations of DNA from laser dissected MM biopsies containing over 80% purity of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, sequencing of HSF4 exon 7 and 8 could not be amplified using vervet DNA template; however, it worked with human and rhesus template. This suggests that certain variants such as large‐scale deletions and rearrangements might have been overlooked due to the shortfalls of normal sequencing which only detects small‐scale variants . It is therefore recommended that more advanced techniques such as multiplex ligation‐dependent probe amplification (MLPA) must be considered for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Multiplex ligation-dependent probe amplification is a better technique to identify large deletions and gene rearrangements, but this technique was not used in our study [37]. Thus, despite a high detection rate, a minority of GCK mutations due to deletions may have been missed in our cohort.…”
Section: Limitationsmentioning
confidence: 99%